Pengembangan Media Komik dalam Pembelajaran IPS pada Materi Peristiwa Lahirnya Pancasila Kelas V SD - Nadia Nofarinda; Murjainah Murjainah; Mega Prasrihamni (STKIP Andi Matappa Pangkep, 2022)
This research aims to produce valid, practical comic media material for the birth of Pancasila class V events, and to determine the potential effects of using comics developed by researchers. The method used in this research is a research and development method. The subjects in this study were class V students, totaling 17 people. Comic media developed using the rowntree model with three stages, namely planning, development, and evaluation. Data collection techniques in this study are questionnaires and learning outcomes tests. Data analysis in this study is the analysis of validity, practicality, and potential effects. The results showed that the comic media that had been developed was declared very valid based on the assessment of the validator consisting of 3 lecturers assessed from all aspects, namely construct, content, and language with the percentage obtained 96.4%. Comic media was declared practical based on student response questionnaires at the one to one and small group stages with a percentage gain of 90% and 94.3% and the developed comic media was declared effective or had a potential effect with a percentage gain of 82%.